1980
DOI: 10.1159/000145266
|View full text |Cite
|
Sign up to set email alerts
|

The interglobular spaces in the endochondral layer of the osseous labyrinth

Abstract: The endochondral layer of the osseous labyrinth in the rat, golden hamster, mouse, guingea pig, pig, rabbit, cat, dog and monkey was studied and compared with that of man. (1) With the exception of the mouse and golden hamster, interglobular spaces were found. (2) In all species but the rat, the interglobular spaces contain acid mucopolysaccharides. An analogy between these structures and the ‘basophilic islands’ (basophile Inseln) is discussed. (3) Extension, arrangement, direction, occurrence and frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Bone matrix autofluorescence intensity at 647 nm allowed delineation of the otic capsule endochondral bone characterized by an interconnected network of macrophage-rich vascular channels connected to reticular bone marrow clusters containing Iba1+ cells and megakaryocytes. The architecture of rat endochondral bone we observed fits with what was characterized in previous studies, where it was found to be very vascularized and enriched in globuli ossei rather than interglobular substance (40). Although the techniques used in these previous studies did not allow labeling of selective immune cell populations nor 3D reconstruction, and therefore bone marrow was not investigated in these studies, comparative measurements of bone properties from these studies suggest that the rat would be the optimal model to study endochondral bone marrow, since endochondral bone vascularization is much higher in rat than in most other animal models (41).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Bone matrix autofluorescence intensity at 647 nm allowed delineation of the otic capsule endochondral bone characterized by an interconnected network of macrophage-rich vascular channels connected to reticular bone marrow clusters containing Iba1+ cells and megakaryocytes. The architecture of rat endochondral bone we observed fits with what was characterized in previous studies, where it was found to be very vascularized and enriched in globuli ossei rather than interglobular substance (40). Although the techniques used in these previous studies did not allow labeling of selective immune cell populations nor 3D reconstruction, and therefore bone marrow was not investigated in these studies, comparative measurements of bone properties from these studies suggest that the rat would be the optimal model to study endochondral bone marrow, since endochondral bone vascularization is much higher in rat than in most other animal models (41).…”
Section: Discussionsupporting
confidence: 87%
“…Given that endochondral and membranous bone differ in collagen I and osteocalcin expression patterns (38), and that both proteins have been observed to be autofluorescent in cleared bone (14), these intensity differences appear to correlate with endochondral bone distribution. As further support of this, around the cochlea the geometry of low-autofluorescence bone (Figures 1C,D) was similar to that of endochondral bone (39) and at high resolution osteon-like layered patterns could be seen in this region (Figure 1E), consistent with the presence of osseous globuli, which predominate in the rat endochondral bone (40). On the other hand, microCT allowed to visualize the distribution of bone marrow cavities but did not allow to observe local variations of bone matrix structure or cavity contents (Figure 1F).…”
Section: Distribution Of Rat Temporal Bone Marrowsupporting
confidence: 68%
See 1 more Smart Citation